(untitled) (Salam International Academic Journal, 2020)
This compressed article on wisdom and its place in Islam contains the ‎following topics‏:‏ First, there is a literal explanation of the concept of wisdom. Next, the ‎spot and place of wisdom, whether wisdom is in the heart or in the mind, ‎is discussed in detail; Experts’ opinions have been put forward, which ‎makes it seem that the place of wisdom is shared between the heart and ‎the head.‎ In the second discussion on the limitations of wisdom, it is argued and ‎proven that there are limits to wisdom and areas where wisdom does ‎not reach and that wisdom cannot achieve hidden cognition ‎‎(clairvoyant) and also in detailed issues, the belief of wisdom ‎independently has no way of knowing them, but rather trusting in ‎revelation.‎ In the third discussion, the importance of wisdom in Islam is discussed ‎in detail about the value of wisdom from the perspective of the Holy ‎Quran in the light of the Qur’anic verses and its value from the prospect ‎of hadiths in the light of detailed prophetic hadiths are deliberated, and ‎it has been proven that Islam does not value wisdom as much as it does ‎not perceive it as a means of perception, but In the Qur’anic scripture, ‎people are called to think and contemplate which is the means of ‎wisdom.‎ The fourth topic of this essay is discussing about mind according to ‎Islamic laws and regulation point of view and the importance, ‎significance of mind is highlighted based on Islamic laws and regulation.‎ Mind, (wisdom, intellect) is a condition for all Islamic ‎obligations (religious assignments).‎ If a person is insane (mad) or having neurosis problem or suffers from ‎mental disorder this person is voided from all kind of ‎obligations (Islamic duties) and it’s good to mention that protecting of ‎mind is Islamic duty, protection of mind means: support, and protection ‎of mind from damaging.‎ The fifth and last topic of this assay is named the interaction of mind and ‎Islamic laws and regulation which is discussing about two fundamental ‎points in details the first points is this that mind always serves Islamic ‎laws and regulation, mind is the tool, medium which is necessity for ‎cognition, understanding of Allah (S.W.T), mind (wise, intellect) is a ‎requirement for acceptance of all Islamic ‎commandments (dispensations) for those who are oblige to perform ‎Islamic laws.‎ Islamic laws(sharia) gives more significance, validity to the mind and ‎kept mind a requirement for performing Islamic assignments and ‎obligations and retain mind as a medium for understanding revelation ‎and Quranic words. The second point is this mind is requirement for ‎revelation.‎ The main function of a mind understands of revelation and its ‎implementation in the life .not bringing changes because the aim for ‎human creation is ruling of the earth and for implementation of this aim ‎there is a need for proper approach that help human being for achieving ‎their goals and these approaches are Quranic verse and revelation that ‎determines the purpose of creation and existence of human being and ‎grant the best approach to achieve that purpose.‎ Concisely, that function, duty and characteristic of revelation is to ‎determine the purpose and the duty of a mind is to perform and ‎implementation.‎